The Role of Short-Termism and Uncertainty Avoidance in Organizational Inaction on Climate Change: A Multi-Level Framework. (February 2017) - Slawinski, Natalie; Pinkse, Jonatan; Busch, Timo; Banerjee, Subhabrata Bobby
Despite increasing pressure to deal with climate change, firms have been slow to respond with effective action. This article presents a multi-level framework for a better understanding of why many firms are failing to reduce their absolute greenhouse gas emissions, which contribute to climate change. The concepts of short-termism and uncertainty avoidance from research in psychology, sociology, and organization theory can explain the phenomenon of organizational inaction on climate change. Antecedents related to short-termism and uncertainty avoidance reinforce one another at three levels—individual, organizational, and institutional—and result in organizational inaction on climate change. The article also discusses the implications of this multi-level framework for research on corporate sustainability.